2020
DOI: 10.6004/jnccn.2020.7546
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Tool to Automate Portions of Pretest Genetic Counseling for Inherited Cancer

Abstract: Background: Increasing demand for genetic testing for inherited cancer risk coupled with a shortage of providers trained in genetics highlight the potential for automated tools embedded in the clinic process to meet this demand. We developed and tested a scalable, easy-to-use, 12-minute web-based educational tool that included standard pretest genetic counseling elements related to panel-based testing for multiple genes associated with cancer risk. Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Although such tools may serve as an effective alternative to inperson counseling [63], it remains critical to maintain quality and study cost-effectiveness in parallel to developing such strategies. In fact, we recently reported on our efforts focused on preliminary testing of a web-based, pretest genetic counseling tool for inherited cancer predisposition [64]. Our results indicated significant increases in knowledge and suggested that most individuals in our clinic-based population felt informed and empowered to make a decision about genetic testing.…”
Section: Strategies To Increase Uptake Of Genetic Counseling and Testmentioning
confidence: 66%
“…Although such tools may serve as an effective alternative to inperson counseling [63], it remains critical to maintain quality and study cost-effectiveness in parallel to developing such strategies. In fact, we recently reported on our efforts focused on preliminary testing of a web-based, pretest genetic counseling tool for inherited cancer predisposition [64]. Our results indicated significant increases in knowledge and suggested that most individuals in our clinic-based population felt informed and empowered to make a decision about genetic testing.…”
Section: Strategies To Increase Uptake Of Genetic Counseling and Testmentioning
confidence: 66%
“…Behaviors (primary outcomes) FC: Self-report of whether they shared their genetic test result with at least one family member for the first time or followed up with family (e.g., gave them relevant information, answered questions, etc.) [59] CRM: Self-report risk management behaviors verified via medical records review to determine if they are congruent with current NCCN guidelines [34,60,61] Awareness and engagement in behavior FC: Several items asking whether they have thought about sharing, chosen to share, and attempted to share and follow-up with family members (response options yes, no, unsure) [62] CRM: Single question asking them to pick one of seven statements that best describes where they are in following medical guidelines [63] Capability (objective knowledge) Both: Inherited cancer testing and treatment knowledge (scores range from 0 to 12 correct) [64,65] Capability (understand how to take action, plan & remember) FC: Likert scale questions (know actions to take, know family members at high risk, clear plan of how, find behavior easy, can remember to act) [62,[66][67][68][69][70][71][72] CRM: Likert scale questions (know actions to take, clear plan of how, find behavior easy, remember to act) [62,66,68,72] Opportunity Last, this study leverages existing novel infrastructure that allows for the recruitment of patients that otherwise may be underrepresented in this type of study (i.e., Blacks, rural dwellers, individuals with low socioeconomic status indicators, and males). Leveraging the TCR offers a population-health approach to recruit participants with P/LP variants in inherited cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, implementation of EHR prompts is a system-based tool that can be used to standardize and automate recommendations based on genetic test results. As a result of our prior work [ 69 , 78 , 84 ], we developed a public facing website ( www.geneshare.net ) to provide tools and resources to enhance family communication of genetic test results. As a further extension of these efforts, we have secured funding to conduct a clinical trial to test interventions focused on guideline-adherent cancer risk management and family communication among those with inherited cancer predisposing genes (NCI U01CA254832).…”
Section: Strategies To Address Increasing Demand For Inherited Cancer Servicesmentioning
confidence: 99%
“…As most hereditary cancer genetic counseling and testing is provided by non-GHPs, this model is supported through non-GHPs partnering with GHPs to provide decision support [77]. Furthermore, technologybased solutions may be used to streamline pre-test genetic education, as we and others have previously reported on [78,79], and is an example of an alternative delivery model (ADM) which has tremendous potential to increase throughput and utilize the expertise of GHPs where they may have the most impact. ADMs were developed to enable genetic counselors to work at the top of their scope of practice while improving access to their services, and various ADMs serve to solve different problems [80].…”
Section: Delivery Of Genetic Counseling and Genetic Testingmentioning
confidence: 99%